From the Ground Up 2012
DOI: 10.1355/9789814345200-009
|View full text |Cite
|
Sign up to set email alerts
|

4 Cultural Heritage and Community Recovery in Post-Tsunami Aceh

Abstract: Our experiences in Aceh lead us to believe that a surprising amount of the reconstruction and development agenda has failed to address the cultural and historical dimensions of social recovery. In spite of all the meetings, coordinating sessions and public statements about interagency cooperation, it is impossible to find a commonly-accepted definition of what 'recovery' entails or should look like. It is difficult to imagine such resources could be allocated and spent 1 without a clearly-defined end-game, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…While it is clear that gampungs have been shaped in part by provincial and national level politics, as well as by the tsunami and unanticipated demands of the reconstruction, many in the post-tsunami environment maintained traditional structures and institutions. Furthermore, in previous research, respondents overwhelmingly identified gampungs as the more logical and appropriate focal point for the conceptualisation and distribution of aid; a finding that was reinforced by respondents interviewed for this paper (Daly and Brassard, 2011;Daly and Rahmayati, 2012;Mahdi, 2012).…”
Section: Assessing the Capacities Of Community Institutionsmentioning
confidence: 69%
“…While it is clear that gampungs have been shaped in part by provincial and national level politics, as well as by the tsunami and unanticipated demands of the reconstruction, many in the post-tsunami environment maintained traditional structures and institutions. Furthermore, in previous research, respondents overwhelmingly identified gampungs as the more logical and appropriate focal point for the conceptualisation and distribution of aid; a finding that was reinforced by respondents interviewed for this paper (Daly and Brassard, 2011;Daly and Rahmayati, 2012;Mahdi, 2012).…”
Section: Assessing the Capacities Of Community Institutionsmentioning
confidence: 69%
“…Reconstruction processes operate within a delicate balance between past and future imaginations and expectations. On one hand, reconstruction can be criticized for focusing excessively on a mission of improvement, contributing to the marginalization of past forms of livelihood, style and traditional practice, as has already been discussed in reference to BRR's own 'Build Back Better' program (Daly and Rahmayati, 2012). But on the other hand, a reconstruction process that aims to erase a destructive event by hoping to return to a pure pre-disaster landscape and livelihood may fail to contribute to disaster mitigation strategies, which require a preservation of knowledge about the threat and an effective transmission of this knowledge, as pointed out in posttsunami research as well (McAdoo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In her discussion of how the 2004 Indian Ocean tsunami was perceived in Southern Thailand, Claudia Merli (2010) argues that her Muslim informants viewed the tsunami simultaneously as an "Act of God," an "Act of Nature," and an "Act of Men and Women." In Aceh the interpretations of the same tsunami event were hotly debated (Daly and R ahmayati 2012;Feener 2013;Miller 2010;Reza 2010). Some Muslim Acehnese suggested that the disaster had taken place as an act of divine retribution for the sins of the people.…”
Section: Contesting Disastersmentioning
confidence: 99%